Fisioterapia respiratoria en la rehabilitación de niños menores de 5 años con enfermedad bronquial obstructiva recurrente que acuden al Hospital IESS Babahoyo - Los Ríos octubre 2019-marzo 2020 - Parrales Benítez, Yilda Teresa (2020)
As an introduction we have that respiratory physiotherapy helps to achieve an improvement of the symptoms getting the maximum performance of each child; With it we improve the speed of airflow for productive cough, we will facilitate the elimination of secretions, this research has as main objective to determine the incidence of physiotherapeutic treatment in the rehabilitation of children under 5 years of age with recurrent obstructive bronchial disease who come to the IESS hospital Babahoyo-Los Ríos October 2019-March 2020, whose methodology used analytically with a qualitative approach, within the results we have that Recurrent Obstructive Bronchial Disease is a disease with a series of symptoms, which damage the respiratory system and this is where the use of physiotherapy comes into play since it is considered important in this group of patients, the same concept is shared by 94%, as a conclusion we have that respiratory physiotherapy directly affects the recovery of the patient with Recurrent Obstructive Disease since it has been demonstrated 94 % have had good results ., and finally a proposal is applied whose theme is: informative talks on the use of respiratory exercises in patients with recurrent obstructive bronchial disease.